Intake of simple sugars as a risk factor for decay in permanent first molars in children - Sutrio Sutrio; Antun Rahmadi; RR. Ratnasari Dyah Purnomowati; Dewi Sri Sumardilah; Roza Mulyani (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Dental caries remains one of the most prevalent oral health problems among school-aged children globally, including in Indonesia. Excessive intake of simple sugars is a major risk factor for dental caries, particularly in the first permanent molars, which erupt early and possess deep pits and fissures that facilitate plaque retention. Purpose: to analyze the relationship between simple sugar intake and the incidence of first permanent molar caries among elementary school students in a stunting locus village in Negeri Sakti. Method: A cross-sectional study was conducted from July to August 2025 involving 150 fourth- and fifth-grade students selected through total sampling. Simple sugar intake was assessed using a 24-hour food recall and analyzed with NutriSurvey. Dental caries examination of the first permanent molars was performed clinically by dental health professionals. Data were analyzed using the Chi-Square test with a significance level of p < 0.05 and Odds Ratio (OR) to determine risk magnitude. Results: Children with high simple sugar intake had a significantly higher risk of developing first permanent molar caries compared to those with low intake (OR = 3.57; p = 0.001). Conclusion: There is a significant relationship between simple sugar intake and the incidence of first permanent molar caries among elementary school children. Reducing simple sugar consumption may play a crucial role in preventing dental caries, particularly in high-risk populations living in stunting locus areas.